1999
DOI: 10.1001/archotol.125.6.615
|View full text |Cite
|
Sign up to set email alerts
|

Mal de Debarquement

Abstract: More than double the number of previously reported cases of mal de debarquement syndrome were identified by this study. The syndrome usually occurs in middle-aged women following an ocean cruise. Symptoms are often refractory to vestibular suppressants as well as physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 10 publications
8
96
2
Order By: Relevance
“…Only 1 of 27 responders to Hain's [7] study and none of Mair's 10 patients were men [14], compared to 16 of 64 (25 %) patients in our series. This proportion was even higher in those with MdD episodes lasting more than 2 years (44 %).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Only 1 of 27 responders to Hain's [7] study and none of Mair's 10 patients were men [14], compared to 16 of 64 (25 %) patients in our series. This proportion was even higher in those with MdD episodes lasting more than 2 years (44 %).…”
Section: Discussionmentioning
confidence: 56%
“…Most cases of MdD reported occurred following cruises, but exposure to other forms of passive motion has also been described [12,14]. Hain reported the largest case series to date in which 27 individuals with symptoms longer than one month underwent a questionnaire survey [7]. These patients did not undergo a neurological exam or vestibular testing; however other reports indicate that neurological exams and vestibular function testing is generally normal in patients with MdD [3,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to be explained by the neural adaptation to the movement in the virtual environment as a post-play after-effect usually related to motion sickness. Perceiving the sensation of motion after being exposed to passive motion typically occurs after traveling on specific vehicles (e.g., boats) and is related to land sickness, post-motion vertigo, and disembarking sickness that can last up to 48 hours (Hain, Hanna, & Rheinberger, 1999). In previous studies, gamers reported feeling their bodies moving when lying in bed after playing (Ortiz de Gortari & Griffiths, 2014a).…”
Section: Altered Body Perceptionsmentioning
confidence: 99%
“…In most cases, the postural complaints subside a few hours after disembarking [86]. However, there are descriptions in the literature of persistent mal de debarquement, lasting from months to years and resistant to anti-motion sickness medications [87,88]. Mal de debarquement may be explained within the framework of multisensorimotor adaptation and habituation to a new or abnormal motion environment.…”
Section: Motion Sickness and Mal De Debarquementmentioning
confidence: 99%